Pre-operative echocardiograms in acute fragility hip fractures: How effective are the guidelines?. Issue 12 (26th March 2021) - AbuSharar, Shady Piedra; Bess, Leah; Hennrikus, Eileen
Abstract : Abstract: In 2014, the American College of Cardiology/American Heart Association (ACC/AHA) released guidelines for ordering pre-operative echocardiograms in patients undergoing non-cardiac surgery. The purpose of this study is to determine if pre-operative echocardiograms ordered prior to fragility hip fracture repair are ordered according to these guidelines, change anesthetic management or affect patient outcomes. In addition, we attempted to evaluate the efficacy of the ACC/AHA guidelines. We conducted a 4-year retrospective chart review of acute fragility hip fractures at a single institution. Charts were reviewed to determine which patients met criteria for a pre-operative echocardiogram. Within this group we then compared patients who received a pre-operative echocardiogram to those who did not. Comparisons were made with regard to time to surgery, changes from standard anesthetic management, major adverse cardiac events, length of hospital stay, and 1-year mortality. We also examined which patients received postoperative echocardiograms and the incidence of adverse cardiac events in this group. Of 402 patients, 87 (22%) had ACC/AHA indications for pre-operative echocardiogram, and 42 (48%) of them received one. The indication to order a pre-operative echocardiogram in stable heart failure or valve disease patients if their last echo was greater than 1 year was only followed 23% of the time. In the pre-operative echocardiogram group, anesthetic management was adjusted more frequently ( P  = .025), and average time to surgery was greater ( P  < .001). The incidence of a major adverse cardiac event was 10% in the ACC/AHA echocardiogram indicated group and 3% in the non-indicated echocardiogram group. An equal number of echocardiograms were completed postoperatively as were completed under ACC/AHA pre-operative guidelines. Sixty-seven percent of the postoperative echocardiograms did not have ACC/AHA pre-operative indications. Our data demonstrates that pre-operative echocardiograms for "stable heart failure and valvular disease with greater than 1 year from last echocardiogram" is infrequently performed without significant adverse cardiac outcomes. Pre-operative echocardiography was associated with more anesthetic adjustments and longer time to surgery. Postoperative echocardiograms were done for cardiopulmonary complications. Studies need to examine and refine clinical parameters that would improve the selection of patients who would benefit from pre-operative echocardiograms.